2005
DOI: 10.5713/ajas.2005.1116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fiber Content and Concentrate Level on Chewing Activity, Ruminal Digestion, Digesta Passage Rate and Nutrient Digestibility in Dairy Cows in Late Lactation

Abstract: The influence of fiber content of hay (low-fiber 47% NDF and high-fiber 62% NDF of DM) and concentrate level (high 50% and low 20% of ration DM) on chewing activity, passage rate and nutrient digestibility were tested on four restrict-fed (11.1 to 13.7 kg DM/d) Holstein cows in late lactation. Aspects of ruminal fermentation and digesta particle size distribution were also investigated on two ruminally cannulated (100 mm i.d.) cows of the same group of animals. All digestion parameters studied were more affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…In addition, the use of elevated proportions of high-quality forages in the diet of dairy cows can help in maintaining high digestible energy intake of the cows despite decreasing concentrate inclusion, which may be beneficial particularly in terms of reducing costs associated with feeding. New studies have demonstrated that increasing the quality of forages by increasing the content of potentially degradable fibre exerts positive effects on production responses in dairy cows (e.g., feed and energy intake and milk production) without compromising rumen conditions (Tafaj et al, 2005;Eastridge, 2006). More recently, Zebeli et al (2006) reported that increasing the amount of degradable organic matter of forages in the TMR enhanced forage intake resulting in higher time spent chewing and ruminating as well as increased milk fat content.…”
Section: Forage Sources In Total Mixed Rationsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the use of elevated proportions of high-quality forages in the diet of dairy cows can help in maintaining high digestible energy intake of the cows despite decreasing concentrate inclusion, which may be beneficial particularly in terms of reducing costs associated with feeding. New studies have demonstrated that increasing the quality of forages by increasing the content of potentially degradable fibre exerts positive effects on production responses in dairy cows (e.g., feed and energy intake and milk production) without compromising rumen conditions (Tafaj et al, 2005;Eastridge, 2006). More recently, Zebeli et al (2006) reported that increasing the amount of degradable organic matter of forages in the TMR enhanced forage intake resulting in higher time spent chewing and ruminating as well as increased milk fat content.…”
Section: Forage Sources In Total Mixed Rationsmentioning
confidence: 97%
“…The fibre quality and particularly its degradability characteristics may positively affect DMI. Enhanced ease of NDF hydrolysis may stimulate rapid turnover of NDF from the rumen and allow greater voluntary feed intake (Allen and Oba, 1996;Tafaj et al, 2005). In addition, Mertens (1994) proposed that NDF be used to define the upper and lower bounds of DMI.…”
Section: Effects Of Dietary Fibre Content and Degradable Starch On Drmentioning
confidence: 97%
“…This is beneficial both economically and health-wise because it lowers the cost associated with feeding, reduces the risk of ruminal disorders and promotes digestion and milk production in dairy cows (Tafaj et al, 2005;Eastridge, 2006). Maize silage (MS) is often viewed as an ideal forage source for dairy cattle because of its high starch and fiber contents and high-yielding properties.…”
Section: Introductionmentioning
confidence: 99%
“…High intake of fibrous feed creates high tention to the rumen wall and stimulate satietary effect and decreases dry matter intake (Toharmat et al, 2006). Low dry matter intake was highly corellated with low nutrien digestibily and the high rate of feed particles passage, which were mostly dictated by the level of fiber intake (Tafaj et al, 2005). A high fiber intake in Timor deer indicated that the deer were addapted and tolerant to the high fiber diet.…”
Section: )mentioning
confidence: 96%